Groundwater investigations in the Hattar Industrial Estate and its vicinity, Haripur district, Pakistan: An integrated approach - Umair Bin Nisar; Muhammad Jahangir Khan; Muhammad Imran; Muhammad Rustam Khan; Muhammad Farooq; Siddique Akhtar Ehsan; Ashfaq Ahmad; Hummad Habib Qazi; Naim Rashid; Tareq Manzoor (Kuwait Journal of Science)
The Hattar industrial estate in the Haripur district, Khyber Pakhtunkhwa (KPK), Pakistan, is investigated for the groundwater potential and aquifer vulnerability using vertical electrical sounding (VES), borehole logs and geochemical data. A total of eight VES points were obtained in the Haripur region using Schlumberger configuration. The interpreted VES models are further constrained by four borehole logs to delineate comprehensive information of the thin lithological layers, subsurface layers configuration, and spatial extent in the area. A quantitative interpretation based on the VES and the borehole data suggests six main subsurface layers; (i) soil cover, (ii) gravel, (iii) clay, (iv) clay with gravel, (v) silty-clay, and (vi) sand with boulder in the study area. A fence diagram is also generated to provide a detailed paleo-depositional model of the subsurface layers. A number of productive groundwater zones are identified across the study area. The interpreted VES data is utilized to compute aquifer thickness, longitudinal conductance, longitudinal resistivity, and transverse resistance within the study area. The lateral extent and protective capacity for the aquifer were inferred from these measurements. The aquifer thickness is relatively low in the central and eastern part ranging from 10 m to 11 m. The longitudinal conductance map shows values greater than 2 mhos from central region to north. This is an indicative of moderate to good protective capacity for the aquifer and is less vulnerable to infiltration of Hattar industrial polluted fluid. However, the values less than 0.19 mhos in the southwest and east are indicative of weak protective capacity with risk of contamination. The geochemical analysis of the surface and subsurface water is carried out at eleven locations to identify the water quality within the study area. The chemical analysis of the water shows presence of the high concentration of Magnesium, bi-carbonate, and Chlorine away from the World Health Organization (WHO) standard.